Pharmacokinetics of Ipatasertib in Subjects With Hepatic Impairment Using 2 Methods of Classification of Hepatic Function. (23rd December 2021) - Sane, Rucha; Malhi, Vikram; Sutaria, Dhruvitkumar S; Cho, Eunpi; Twomey, Patrick; Craggs, Christopher; Wang, Jianshuang; Harris, Adam; Musib, Luna
Abstract: Ipatasertib is a highly selective small‐molecule pan‐Akt inhibitor in clinical development. Ipatasertib is predominantly eliminated by the liver, and therefore, the effect of hepatic impairment on ipatasertib pharmacokinetics (PK) was evaluated. In this phase 1 open‐label, parallel group study, the PK of ipatasertib were evaluated in subjects with hepatic impairment based on both the Child‐Pugh and the National Cancer Institute Organ Dysfunction Working Group classification for hepatic impairment. A single dose of ipatasertib at 100 mg was administered and the PK was characterized in healthy subjects with normal hepatic function or mild, moderate, and severe hepatic impairment. Based on Child‐Pugh classification, subjects with moderate and severe hepatic impairment had an ≈2‐ and 3‐fold increase in systemic exposure (area under the plasma concentration–time curve from time 0 to infinity [AUC0‐∞ ]) to ipatasertib, respectively, compared to subjects with normal hepatic function. Systemic exposure (AUC0‐∞ ) to ipatasertib in subjects with mild hepatic impairment was comparable to that in subjects with normal hepatic function. In accordance with reduced clearance capacity, subjects with mild to severe hepatic impairment showed lower systemic exposure (AUC0‐∞ ) of ipatasertib metabolite M1 (G‐037720). Overall results were comparable between Child‐Pugh and National Cancer Institute Organ Dysfunction Working Group classification criteria. Based on the results from this study, no dosage adjustment is required for ipatasertib when treating patients with mild hepatic impairment, whereas a dose reduction would be recommended for subjects with moderate or severe hepatic impairment. Based on real‐world data analysis, ≈2% of the intended patient population is expected to need a modified dose due to moderate or severe hepatic impairment.